The UNIfy Program: Providing Additional Support to Students With Mental Health Issues in a University Context - Jocelyn Courtney (JANZSSA)
As student population numbers increase in tertiary institutions, so does the number of students presenting with diagnosed and undiagnosed mental health issues. According to the ABS (2008), 4.1% of the general population experience depressive episodes and 14.4% are diagnosed with anxiety disorders. However, students attending regional universities such as the University of the Sunshine Coast are at a greater risk of developing a mental illness due to factors such as social isolation, relocation and financial difficulties. A recent study (Mulder & Cashin, 2015) indicated that 16% of the student cohort in a regional university in Australia presented in very high levels of distress. Considering the high volume of students presenting with mental health issues compared to the general Australian population, it is imperative that universities invest in the overall health of its students to improve retention rates, academic results, career outcomes, general wellbeing, and student satisfaction.